Transition issues in higher education and digital technologies: the experiences of students with disabilities in New Zealand. Issue 2 (7th February 2021) - Pacheco, Edgar; Yoong, Pak; Lips, Miriam
Abstract: Research on transition to higher education and young people with disabilities has increased in recent years. However, there is still limited understanding of transition issues and how digital technologies, such as social media and mobile devices, are used by this group of students to manage these issues. This article presents the findings of an empirical study that addressed this matter based on young people's views and experiences. The qualitative study was conducted in the context of a group of students with vision impairments transitioning to a New Zealand university. The findings draw from observations, a researcher diary, focus groups, individual interviews, and data from social media. The study shows that, like their non-disabled peers, the students actively engaged with interactive and collaborative digital technologies to make sense, individually and collectively, of different transition issues before, during and after the first academic trimester of their university journey. Points of interest: This research shows that, from the perspective of students with vision impairments, key issues for transitioning to higher education include the academic system, social connections, disability support, family involvement and their own impairment(s). Transition issues in higher education, in the context of disability, are complex and interconnected. Students with vision impairments actively engage with and adapt digital technologies to manage transition issues. These findings expand the current understanding of transition as well as student retention in higher education in the context of disability and the role of digital technologies. This research recommends tertiary institutions use creatively collaborative and interactive digital technologies to complement transition services and activities for students with disabilities so their participation and inclusion in higher education can be encouraged.